An Assessment of Ecological Sensitivity and Landscape Pattern in Abandoned Mining Land - Shi, Yu; Fan, Xiaoxiao; Ding, Xiaoying; Sun, Meiqi (Sustainability, 2024)
In recent years, the development of abandoned mining land has become a focal point in landscape planning. However, during the development of abandoned mining land, there often exists a phenomenon of prioritizing economic considerations over ecological concerns, leading to a failure to achieve genuinely sustainable development. An ecological sensitivity assessment, guided by the principles of protection and development, provides an evaluation framework that directs planning strategies for abandoned mining land from the perspective of balanced development and conservation. To facilitate the development and construction of abandoned mining land, this paper utilizes GIS technology, on-site surveys, analytic hierarchy processes, etc. Taking the abandoned mining land in Haining, Zhejiang, China, as the research subject and considering its unique site conditions, ecological sensitivity is divided into topographic conditions, surface water systems, and plant landscapes. Ecological sensitivity factors are selected, and an ecological sensitivity assessment system is constructed from the perspectives of ecological conservation and sustainable development. Using ArcGIS 10.2 and Fragstats 4.2 software, landscape pattern analysis is conducted, exploring the relationship between landscape patterns and ecological sensitivity assessment results from the perspectives of landscape fragmentation, diversity, and aggregation. By comparing the results of single-factor sensitivity analysis and comprehensive sensitivity analysis, as well as landscape pattern indices before and after classifying ecologically sensitive areas, the practicality of the evaluation system is verified, facilitating planning studies and providing design recommendations for abandoned mining land. Landscape pattern indices serve as supplementary explanations for ecological sensitivity. Based on the results of ecological sensitivity assessment and landscape pattern indices, the ecological conservation levels in the research area are classified into five categories: the Level I Comprehensive Protection Zone, Level II Moderately Developed Zone, Level III Construction Suitable Zone, Level IV Core Construction Zone, and Level V Core Development Zone. These correspond to ecological protection zones, sightseeing experience zones, historical exhibition zones, core commercial zones, and themed amusement zones, respectively. The I-level sensitive area in the research area has the smallest range, while IV-level and VI-level sensitive areas have larger extents, exhibiting a high degree of overall landscape fragmentation but with diverse and dominant landscape types. Integrating ecological sensitivity assessment results and landscape pattern indices aids in delineating ecological conservation levels and regional functional recreation zones, guiding the rational recreation allocation of resources for abandoned mining land and promoting its development into a scenic area integrating ecology and tourism.